(untitled) (Journal of the Bangladesh Agricultural University, 2024)
This study attempted to explore the impact of broiler farming on livelihood improvement of the selected broiler farmers of Bhaluka upazila (sub-district) under Mymensingh district by analyzing factors influencing key indicators of livelihood change like food availability, household conditions, physical assets, sanitation, and income. A total of 60 randomly selected broiler farmers was considered for the sample of this study, from whom data were collected using a structured questionnaire by a face-to-face interview from October to November 2022. The paired sample t-test and total livelihood score were considered for overall livelihood change. The findings underscore significant positive changes in livelihood dimensions following broiler farming adoption. It was found that the mean of the overall livelihood scores before (13.55) and after (18.02) situation reveals the improvement of livelihood status, which is further supported by the significant t-value (18.626). There was notable improvement in food availability, upgraded household conditions, increased physical assets, enhanced sanitation, and elevated income levels. Despite these positive outcomes, the study highlighted persistent challenges, particularly in disease outbreaks and high input costs. In addition to recognizing and resolving current issues, it highlighted how broiler farming may improve a variety of livelihoods in Bangladesh. Through shedding light on both successful outcomes and enduring challenges, the study helped shape strategies for promoting rural development and sustainable farming methods in the context of broiler farming. J Bangladesh Agril Univ 22(4): 468-479, 2024